EFEKTIVITAS UNDANG-UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN KHUSUSNYA MENGENAI LARANGAN PENGGUNAAN TELEPON GENGGAM SELAMA PENERBANGAN BERLANGSUNG - I KADEK ADI SURYA (Universitas Mahasaraswati K. Mataram, 2022)
Aviation is one of the means of transportation used by the community in meeting the needs of the traveling sector in cross-country and national and international traffic, air transportation is the main choice in traveling when the community has little time constraints to travel to the desired location, but in the world Aviation does not deny that there is an accident in flight, the causal factors are due to human error or human actions, weather conditions, infrastructure that is very outdated, but in the discussion of this study the author focuses on the causes of accidents in the world of aviation due to human error in this case using cell phones during the flight, although Law Number 1 of 2009 concerning Aviation has prohibited the use of cell phones during flights, the public and officers are still unable to access mobile phones. implementing these regulations due to a lack of knowledge related to the prohibitions contained in the Aviation Law, so that in this study the author uses a normative juridical research method where this research analyzes problems and points of view or according to the provisions of the applicable law or legislation. Normative legal research discusses legal doctrines or principles in legal science, with this method the authors are interested in discussing the effectiveness of Law Number 1 of 2009 concerning Aviation, especially regarding the prohibition of using mobile phones during flights